韩素音译介观的时代意义—— 以中国大陆的历史文化语境为背景 ＝ The significance of Han Suyin’s views on translation in the historical and cultural context of mainland China - 崔峰 Cui Feng (八方文化创作室 Global publishing, 2019)
本文以1950年代到21世纪中国大陆历史文化语境为背景，从三个阶段观察韩素音的译介活动、译介观，即第一阶段：1950-1970年代：“冷战”格局下对中国社会与国家领导人的译介；第二阶段：1980-1990年代：翻译工作的艺术性与创造性；第三阶段：1990年代-21世纪：培养翻译人才使用中国文化“走出去”，从而观察到韩素音的译介观或契合了当时社会翻译活动发展的需要，或紧扣时代发展前进的脉搏而具有一定的前瞻性。她对中国社会翻译界的贡献影响深远，其诸多翻译思想在当下乃具现实意义，值得我们不断借鉴与思考。 Set against the historical and cultural context of Mainland China from the 1950s to the 21st century, this paper examines the three stages of Han Suyin’s views on medio-translatology and her involvement in this field. The first stage (1950s - 1970s): translation approach towards the Chinese society and its leaders in the context of the Cold War; the second stage (1980s - 1990s): translation as the art of rewriting; the third stage (1990s - 21st century): nurturing adept translators to facilitate the “stepping out” of Chinese culture. It can be inferred that Han Suyin’s views on translation was a timely contribution to the development of the translation field at that time, and was also far-sighted in that her views had kept in tandem with the changing times. Han Suyin has certainly made enduring contributions to the Chinese field of translation. Given that most of her views on translation are still of practical relevance today, it offers us invaluable lessons to learn and reflect upon.